(untitled) (Geneva, 1992)
Content: The study covers three industres: the machinery manufaturing, printing and banking industries. Each monograph consists of case- studies on selected enterprise in these industries. The study show that throughout the introduction of technological change there was greater continuity and stability in labour relations sytems providing for problem- solving through worker's participation than in those relying exclusively, or predominantly, on the establishment and application of standard, for instance collective bargaining and grrievance procedures.
Keywords: Employees,Industrial relations,Quan hệ lao động; Effect of technological innovations on,Case studies,Case studies,Nghiên cứu